PLASMA ADIPONECTIN LEVEL AND CORRECTED QT INTERVAL IN SMOKER AND NON-SMOKER ADULT MALE SUBJECTS - Theint, Yin-Thu; Khin, Ei-Ei; Sein, Mya-Thanda (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Animal studies reported that adiponectin plays a role in expression of potassium channel and duration of action potential in ventricular muscles. Only few studies are available focusing on role of adiponectin in QTc interval in human study. This study aimed to investigate the plasma adiponectin level and corrected QT interval (QTc) in smokers and non-smokers. METHODOLOGY This cross-sectional analytical study was undertaken in 30 smokers (age: 26.5±4.1 years, body mass index (BMI): 21.67±1.66 kg/m2 ) and 30 non-smokers (age: 25.4±3.52 years, BMI: 20.95±2.1 kg/m2 ). Plasma adiponectin level was determined by enzyme-linked immunosorbent assay (ELISA). The QT interval was measured by routine 12-lead ECG with Lead II rhythm and QTc was calculated. RESULTS Plasma adiponectin level was significantly lower in smokers (27.89±15 µg/ml) than that of non-smokers (52.13±21.57 µg/ml) (p<0.001). A significant increase in QTc interval was seen in smokers (415.37±29.90 vs 395.63±26.13 ms, p<0.01). A significant negative correlation between plasma adiponectin level and QTc interval was observed in the whole study group (n=60, r= -0.407, p=0.001). The risk of low adiponectin levels in smokers was 8.1 times higher than non-smokers (odds ratio (OR) =8.1, 95% confidence interval (CI) =1.61-40.77) whereas the risk of QTc prolongation in smokers was 6 times higher than non-smokers (OR=6, 95% CI=1.17-30.73). Risk of QTc interval prolongation was 4.3 times increased in low adiponectin group than normal adiponectin group (OR=4.27, 95% CI=1.05-17.46). CONCLUSION Smokers have greater risk for low plasma adiponectin level and prolonged QTc interval. Decreased adiponectin level might partly contribute to prolonged QTc interval in smokers.